Trends and Maps of Research Collaboration on Teacher Digital Literacy and Student Digital Citizenship: Bibliometric Analysis - Tita Setiawati; Atep Sujana; Rama Wijaya Abdul Rozak; Cica Yulia; Elih Sudiapermana (SOSIOEDUKASI, 2025)
This study aims to identify trends, main topics, and patterns of scientific collaboration in the study of teachers' digital literacy and students' digital citizenship. Using bibliometric methods, this study analyzed scientific publications obtained from the Scopus database during the period 2016–2025. The data collected includes information about titles, authors, year of publication, keywords, affiliations, and journal sources. The analysis was conducted using VOSviewer software to map collaboration networks between researchers and between countries, as well as identify keywords that frequently appear in related publications. The results of the study show that teachers' digital literacy is a topic that has experienced a significant increase, especially since 2020, in line with the increasing need for digital learning during the pandemic. Meanwhile, studies on student digital citizenship are still relatively few but show a steady upward trend. The most frequently appearing keywords include "digital literacy", "digital citizenship", "teachers", "students", and "digital competence". Collaboration between countries is dominated by the United States, followed by countries such as the United Kingdom, Canada, China, and Australia. Indonesia began to engage in collaborative networks, albeit on a limited scale. This study provides a comprehensive overview of the direction and development of research, as well as identifying opportunities for further study in the field of digital literacy and digital citizenship in the context of education.